Repetitive DNA sequences accelerate molecular cytogenetic research in plants with small chromosomes - Agus Budi Setiawan; Ari Wibowo; Chee How Teo; Shinji Kikuchi; Takato Koba (Universitas Gadjah Mada, 2019)
Repetitive DNA sequences are highly abundant in plant genomes and are favorable probes for chromosome identification in plants. However, it is difficult to conduct studies on the details of metaphase chromosome structures in plants with small chromosomes due to their highly condensed status. Therefore, identification of homologous chromosomes for karyotyping and analyzing chromosome structures is a challenging issue for cytogeneticists without specific probes and precise chromosome stages. In this study, five repetitive DNA probes, i.e., 5S and 45S ribosomal DNAs (rDNAs), melon centromeric sequence (Cmcent), cucumber subtelomeric sequence (Type I), and microsatellite (CT)10 repeats, were used to identify primary constrictions and homologous chromosomes for karyotyping. Four and two loci of 45S rDNA were respectively observed on metaphase and pachytene chromosomes of Abelia × grandiflora. Cmcent was detected on both primary constrictions of melon pachytene and metaphase chromosomes. Furthermore, one pair of 5S rDNA signals were hybridized on melon metaphase chromosomes. Eight and two loci of 45S and 5S rDNA were respectively detected on cucumber chromosomes. Type I and (CT)10 probes were specifically hybridized on subtelomeric and interstitial regions on the chromosomes, respectively. These results suggest that repetitive DNA sequences are versatile probes for chromosome identification in plants with small chromosomes, particularly for karyotyping analyses.